Edupreneurship Based on Local Toraja Wisdom to Strengthen Students’ Learning Needs in Facing The Digital Era - Shilfani Shilfani; Markus Deli Girik Allo; Mey Enggane Limbongan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The Covid-19 pandemic that hit the world in the midst of the digital era has resulted in setbacks in various aspects, especially the education and entrepreneurship sectors. Edupreneurship based on local wisdom is expected to be one of the answers and solutions to increase the rate of economic growth affected by the post-pandemic. Through learning that focuses on local values, ideas, and culture to create a character who is resilient, wise, skilled and innovative so as to produce new business opportunities and breakthroughs. The Edupreneurship course is compulsory and is taught in semesters three, five and seven at the UKI Toraja English Study Program as a form of manifestation of the vision and mission of the English study program. The general purpose of the Edupreneurship course is that after the end of learning this course, students are expected to be able to master and practice values and attitudes related to entrepreneurship education. For example, characters with integrity, enthusiasm, not easy to give up, accomplished, independent, earned, and test-resistant in facing various conditions. To achieve these general goals, of course, various aspects of the learning process must be considered and prepared by teachers. These things are the elaboration and achievement of specific objectives of each sub-topic of the material, teaching and learning activities, the use of media and teaching tools, the implementation of teaching strategies, and up to the evaluation stage. The result of the purpose of this research is to identify the strengthening of students' learning needs in facing the digital era through edupreneurship based on local wisdom. The method used in this study is a qualitative method. This research will focus on efforts to create entrepreneurship education products based on local wisdom values. In collecting data, researchers will use qualitative research instruments. After conducting data analysis, the researcher will draw a conclusion about "Edupreneurship based on Toraja Local Wisdom as Strengthening the Learning Needs of Students in the Digital Era".